" Cultural Alienation among University Youth in the Light of Globalization"Case Study: A Sample of Sociology Department Students at Tishreen University (Damascus University Journal of arts and humanities sciences, 2026)
The research aims to study the phenomenon of cultural alienation among university youth in light of globalization. To achieve this goal, the descriptive analytical approach was used, a social survey with a sample, and a regular random sample of students from the Department of Sociology at Tishreen University was drawn, numbering (250) male and female students. The cultural alienation scale was used as a study tool, prepared by the researcher, with (30) phrases in order to determine the level of cultural alienation among students, monitor the reasons leading to it and helping to spread it, as well as describe some aspects of alienation among students. After collecting the data, it was unloaded and analyzed using the SPSS program and reached a set of results, the most important of which were: that the level of cultural alienation among students was average, and the most important reasons that helped in this were technology and communications through what it broadcasts of Western culture and disseminates among students, through its own media aswell as through social platforms and social media. The most important manifestations of this alienation were the students’ separation from their local culture through the use of foreign terms in their conversations, as well as their clothing, dress, and way of thinking, which began to move away from The local culture, its customs and traditions, and tends towards Western culture. The results also showed differences between the average scores of the sample members' answers according to the gender variable in favor of females, and the original place of residence in favor of the city. There were no differences according to the current place of residence. At the end of the research, a set of proposals were presented that would raise the level of youth's connection to their local culture and work to reduce the level of cultural alienation among them in light of globalization.
Keywords: Alienation; Cultural Alienation; University Youth; Globalization; Cultural Globalization